Considerations for Maximizing Perioral Aesthetics in Gender-Affirming Surgery - Thielhelm, Torin; Liu, Katherine; Mavrommatis, Maria; Rosenberg, Joshua D. (Facial Plastic Surgery, 2025)
Perioral aesthetics are a critical component of facial gender-affirming surgery (FGAS). The goal of this paper is to review the philosophy, techniques, and evidence supporting perioral aesthetics in FGAS with specific attention to the lips, chin, and submentum.Masculine appearance is typically associated with greater upper lip height, labial volume, and mouth width, whereas female appearance exhibits increased upper incisor show with a softer, tapered chin shape. The masculine chin is wider and taller with greater anterior projection, whereas the feminine chin is typically more narrowed. The contour of the submentum is impacted by skeletal and soft tissue differences, with males displaying a more angular profile.Techniques for lip feminization include the subnasal lip lift and various injectables for altering lip contour. For chin contouring, several genioplasty techniques exist, including the T-genioplasty. These procedures may utilize virtual surgical planning. Submental liposuction and platysmaplasty can refine the submental area to highlight underlying osseous structures. Augmentation of the mandible, typically using implants, can be utilized for masculinization of the perioral region.Careful attention to the lips, chin, and submentum can help achieve desired outcomes in both facial feminization and masculinization. A comprehensive understanding of perioral anatomy and an individualized technique selection are vital for achieving optimal FGAS outcomes.
Keywords: perioral aesthetics; facial feminization; gender affirmation; virtual surgical planning